Miscellanea: VII (Catholic record society, 1914)
Thomas Wiseman; Cardinal Allen; Priests in England and Wales, 1692; Six Catholics, 1596-1637; Spanish Embassy, 1614; Christchurch-Twineham; Monmouth Mission; John Hambly; Eccles family; Registers of St. Mary's Highfield Street, Liverpool, 1741-73; English Benedictine nuns in Paris, now at Colwich, Staffs.